Proceedings of the 58th Annual Meeting of the Association for Computational Linguistics 2020
DOI: 10.18653/v1/2020.acl-main.647
|View full text |Cite
|
Sign up to set email alerts
|

Null It Out: Guarding Protected Attributes by Iterative Nullspace Projection

Abstract: The ability to control for the kinds of information encoded in neural representation has a variety of use cases, especially in light of the challenge of interpreting these models. We present Iterative Null-space Projection (INLP), a novel method for removing information from neural representations. Our method is based on repeated training of linear classifiers that predict a certain property we aim to remove, followed by projection of the representations on their null-space. By doing so, the classifiers become… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
291
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 167 publications
(296 citation statements)
references
References 28 publications
(39 reference statements)
5
291
0
Order By: Relevance
“…They conclude that adversarial learning alone does not guarantee invariant representations for the protected attributes. Ravfogel et al (2020) found that iteratively projecting word embeddings to the null space of the gender direction to further improve the debiasing performance.…”
Section: Related Workmentioning
confidence: 99%
“…They conclude that adversarial learning alone does not guarantee invariant representations for the protected attributes. Ravfogel et al (2020) found that iteratively projecting word embeddings to the null space of the gender direction to further improve the debiasing performance.…”
Section: Related Workmentioning
confidence: 99%
“…Splitting the representations into components is done using INLP (Ravfogel et al, 2020), an algorithm for removing information from vector representations.…”
Section: Dissecting Mbert Representationsmentioning
confidence: 99%
“…Such studies on model bias have led to many bias mitigation techniques (e.g., Bolukbasi et al, 2016b;Dev et al, 2020a;Ravfogel et al, 2020;Dev et al, 2020b). In this work, we focus on exploring biases across QA models and expect that our framework could also help future efforts on bias mitigation.…”
Section: Related Workmentioning
confidence: 99%